UJI VIABILITAS MIKROENKAPSULASI Lactobacillus casei MENGGUNAKAN MATRIK NATRIUM ALGINAT - Nelly Suryani; Ofa Suzanti Betha; Qurry Mawaddana (JFL : Jurnal Farmasi Lampung, 2019)
Lactobacillus casei is a species that is often used as a probiotic but is not resistant to very acidic environments. Microencapsulation in this study was carried out using the extrusion method with a matrix of sodium alginate concentrations of 2%, 3%, and 4%. The three concentrations of sodium alginate were tested for their ability to protect Lactobacillus casei ATCC 393 from the effects of gastric acid simulation fluid. From the viability test, the results of enumeration of cells in the concentration of sodium alginate 2%, 3% and 4% were 3.08 x 106 colonies / gram; 7.41 x 104 colonies / gram; and 1.01 x 107 colonies / gram. The three MLNs with the three concentrations were incubated in gastric acid simulation fluid (0.08 M HCl; 0.2% NaCl; pH 1.5) for 120 minutes. The enumeration results of MLN viability after testing the gastric acid liquid at a concentration of 4% were 4.5 x 103 colonies / gram, whereas at a concentration of 2% and 3% the viability value was